Utility of Reactive Species Generation in Plasma Medicine for Neuronal Development - Sarmistha Mitra; Neha Kaushik; Il Soo Moon; Eun Ha Choi; Nagendra Kumar Kaushik (Biomedicines, 2020)
Reactive oxygen species (ROS) are critical signaling molecules for neuronal physiology that stimulate growth and development and play vital roles in several pathways when in a balanced state, but they cause neurodegeneration when unbalanced. As ROS levels above a certain threshold cause the activation of the autophagy system, moderate levels of ROS can be used as treatment strategies. Currently, such treatments are used together with low-level laser or photodynamic therapies, photo-bio modulation, or infrared treatments, in different chronic diseases but not in the treatment of neurodegeneration. Recently, non-thermal plasma has been successfully used in biomedical applications and treatments, and beneficial effects such as differentiation, cell growth, and proliferation, stimulation of ROS based pathways have been observed. Besides the activation of a wide range of biological signaling pathways by generating ROS, plasma application can be an effective treatment in neuronal regeneration, as well as in neuronal diseases. In this review, we summarize the generation and role of ROS in neurons and provide critical insights into their potential benefits on neurons. We also discuss the underlying mechanisms of ROS on neuronal development. Regarding clinical applications, we focus on ROS-based neuronal growth and regeneration strategies and in the usage of non-thermal plasma in neuronal and CNS injury treatments.